(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Benign laryngeal lesions are a major cause of dysphonia and are associated with significant morbidity. These lesions arise from a complex interplay of behavioral, environmental, and physiological factors. Objective: To evaluate the demographic profile, etiological factors, clinical presentation, and management outcomes of benign laryngeal lesions. Methods: A prospective observational study was conducted on 50 patients presenting with symptoms suggestive of benign laryngeal lesions at a tertiary care center between November 2018 and May 2020. All patients underwent detailed clinical evaluation, videolaryngoscopy, and histopathological examination where indicated. Results :The majority of patients were in the 21–40-year age group (58%), with a male predominance (62%). Voice abuse (68%) was the most significant etiological factor. Vocal cord polyps (36%) were the most common lesions, followed by nodules (26%). Conservative management was effective in early lesions, while surgical intervention was required in 66% of cases. Overall improvement was observed in 76% of patients. Conclusion: Benign laryngeal lesions are predominantly non-neoplastic and strongly associated with modifiable risk factors. Early diagnosis and tailored management strategies result in favorable outcomes.